2013
DOI: 10.1021/bm401302v
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Protein–Protein Associations

Abstract: While traditional models of protein adsorption focus primarily on direct protein-surface interactions, recent findings suggest that protein-protein interactions may play a central role. Using high-throughput intermolecular resonance energy transfer (RET) tracking, we directly observed dynamic, protein-protein associations of bovine serum albumin on poly(ethylene glycol) modified surfaces. The associations were heterogeneous and reversible, and associating molecules resided on the surface for longer times. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 69 publications
8
45
0
Order By: Relevance
“…For example, in previous work, transient protein−protein associations were observed to increase the surface residence time for BSA on a PEG monolayer at protein concentrations as low as 2.5 × 10 −6 mg/mL. 45 Although molecular fluorescence intensity serves as only a lower estimate of oligomerization state when unlabeled proteins are present, we saw both fluorescently labeled monomers and oligomers at high protein concentrations on the surface (see the Supporting Information). For both monomers and oligomers, we observed shorter residence times at high protein concentrations.…”
Section: Increased Protein Concentrations Leads Tomentioning
confidence: 53%
See 1 more Smart Citation
“…For example, in previous work, transient protein−protein associations were observed to increase the surface residence time for BSA on a PEG monolayer at protein concentrations as low as 2.5 × 10 −6 mg/mL. 45 Although molecular fluorescence intensity serves as only a lower estimate of oligomerization state when unlabeled proteins are present, we saw both fluorescently labeled monomers and oligomers at high protein concentrations on the surface (see the Supporting Information). For both monomers and oligomers, we observed shorter residence times at high protein concentrations.…”
Section: Increased Protein Concentrations Leads Tomentioning
confidence: 53%
“…In previous work, we demonstrated that dynamic protein−protein interfacial associations occurred at solution concentrations as low as 2.5 × 10 −6 mg/mL for BSA on a PEG monolayer (at a surface coverage of 2.5 molecules per μm 2 ). 45 In the experiments described in this section, protein solution concentrations were increased to 0.3 mg/mL for IgG and 1.0 mg/mL for BSA by mixing unlabeled protein and low concentrations of fluorescently labeled protein (10 −5 −10 −6 mg/mL). Labeled proteins served as reporter molecules of interfacial dynamics at these high protein concentrations.…”
Section: Increased Protein Concentrations Leads Tomentioning
confidence: 99%
“…It is however necessary to recognize that all differences between specified biochemical equilibria and rates within an intact cell and the same equilibria and rates in a dilute solution of purified macromolecules cannot and should not be attributed to crowding. One cannot ignore the likelihood of additional modulating effects deriving from interactions of soluble macromolecules with membranes and other structural elements 69 , in addition to unidentified or incompletely characterized interactions between the studied reactants and other soluble species such as molecular chaperones 10 . Thus we would like to make clear at the outset that the term macromolecular crowding should be used to describe only those effects arising from the presence of a total high weight per volume concentration of functionally unrelated soluble macromolecules.…”
Section: What Is Macromolecular Crowding?mentioning
confidence: 99%
“…86 Due to the significant uncertainty in the parameter μ and the absolute fluorescence intensities, we reported our data using the relative end-to-end distance d = r/μ = (F D /F A ) 1/6 as in previous single-molecule FRET studies of freely adsorbing molecules. 54,55,83,87 Calculation of Likelihood of Conformational States. For a data set with N total observations, the likelihood of observing a helix is n(helix)/N, where n(helix) is the number of observations of the helix state.…”
Section: Articlementioning
confidence: 99%